The liminal chrysalis : imagining reproduction and parenting futures beyond the binary - Doty, H. Kori; Lowik, A. J. (Demeter Press, 2022)
The Liminal Chrysalis: Imagining Reproduction and Parenting Futures Beyond the Binary is an edited collection that works to identify and deconstruct many of the countless binaries that operate within the realms of parenting and reproduction. Weaving poetry, speculative fiction, and autobiography, with interviews, critical analysis and research, the authors take as their starting place that there is magical potential and possibility in the ambiguous, disorienting spaces of the in-between and the beyond. The collection challenges the constructedness of binaries connected to sex, gender, sexualit.